Pengaruh Atmosfer Coffeeshop Ekara terhadap Pengalaman Wisata Anak Muda di Bandung - Muhammad Raihan Fatahillah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The phenomenon of “nongki,” a colloquial term for hanging out, has become an integral part of today’s youth lifestyle. This activity is not only about passing the time but also functions as a medium for social interaction, idea exchange, and even content creation for social media. Among various hangout spots, coffee shops have emerged as the most favored places for young people. Coffee shops are chosen not only for their beverage and snack offerings but also for their cozy, aesthetic ambiance and supportive facilities such as Wi-Fi and power outlets. These advantages make coffee shops an ideal place for social gatherings, studying, and even working. This study aims to describe young people's preferences for coffee shops as hangout spots and analyze the factors that make them superior to other options like food stalls, city parks, or food courts. Observational findings reveal that beyond menus and location, interior design, customer service, and digital accessibility are key determinants in selecting coffee shops.